Prendre souffle dans le limon du fleuve: Saint-Laurent mon amour de Monique Durand - Modenesi, Marco (Ponti/Ponts, 2021)
Saint-Laurent mon amour is a long ode in prose to Saint Lawrence River and all its riverside residents. Composed by short stories, memories and impressions from the past and from the present, the book underlines the influence, the importance and the role that the river has in the life of many people; ordinary and extraordinary people who belong to the story and the history of Quebec. Monique Durand shows how deep are the ties between Quebec and its main river.